Does Radar Technology Support the Diagnosis of Pneumothorax? PneumoScan—A Diagnostic Point-of-Care Tool. (25th September 2013) - Lindner, T.; Conze, M.; Albers, C. E.; Leidel, B. A.; Levy, P.; Kleber, C.; De Moya, M.; Exadaktylos, A.; Stoupis, C.
Abstract : Background . A nonrecognized pneumothorax (PTX) may become a life-threatening tension PTX. A reliable point-of-care diagnostic tool could help in reduce this risk. For this purpose, we investigated the feasibility of the use of the PneumoScan, an innovative device based on micropower impulse radar (MIR). Patients and Methods . addition to a standard diagnostic protocol including clinical examination, chest X-ray (CXR), and computed tomography (CT), 24 consecutive patients with chest trauma underwent PneumoScan testing in the shock trauma room to exclude a PTX. Results . The application of the PneumoScan was simple, quick, and reliable without functional disorder. Clinical examination and CXR each revealed one and PneumoScan three out of altogether four PTXs (sensitivity 75%, specificity 100%, positive predictive value 100%, and negative predictive value 95%). The undetected PTX did not require intervention. Conclusion . The PneumoScan as a point-of-care device offers additional diagnostic value in patient management following chest trauma. Further studies with more patients have to be performed to evaluate the diagnostic accuracy of the device.